Percepción de la violencia de género en mujeres de la comunidad Cofán Dureno de la provincia de Sucumbíos - Flores, Jorge A. (2021)
Gender-based violence is a current problem, with a high impact and incidence, which affects millions of women around the world, and, more significantly, who present particular conditions of vulnerability. one of the groups especially prone to suffering this form of violence in the context of countries Hispanic Americans, is that of women belonging to indigenous cultures, who, Historically, they have been invisible and relegated. One could then say "... they face a triple disadvantage: being women, being poor and being indigenous; immersed in a context where male domination stands out” (Nava et al., 2017, p.162).